2014
DOI: 10.1101/lm.036517.114
|View full text |Cite
|
Sign up to set email alerts
|

The role of the medial prefrontal cortex in trace fear extinction

Abstract: The extinction of delay fear conditioning relies on a neural circuit that has received much attention and is relatively well defined. Whether this established circuit also supports the extinction of more complex associations, however, is unclear. Trace fear conditioning is a better model of complex relational learning, yet the circuit that supports extinction of this memory has received very little attention. Recent research has indicated that trace fear extinction requires a different neural circuit than dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 83 publications
1
14
0
Order By: Relevance
“…For CS tests, the percent time freezing during each 30-sec CS presentation was calculated and the average freezing during the first 4 discrete CS presentations was used for statistical analysis. We chose to use the first 4 CS presentations because extinction appeared to begin after the 4 th trial for both training types, consistent with results we have previously observed (Kwapis et al, 2015; Kwapis et al, 2014). Each training group was analyzed separately and drug differences in freezing were analyzed using t-tests (context tests) or mixed-model ANOVAs (CS tests) with a repeated measure of Period (baseline vs. CS period of the test session) and a between factor of Drug (vehicle or ANI/APV).…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…For CS tests, the percent time freezing during each 30-sec CS presentation was calculated and the average freezing during the first 4 discrete CS presentations was used for statistical analysis. We chose to use the first 4 CS presentations because extinction appeared to begin after the 4 th trial for both training types, consistent with results we have previously observed (Kwapis et al, 2015; Kwapis et al, 2014). Each training group was analyzed separately and drug differences in freezing were analyzed using t-tests (context tests) or mixed-model ANOVAs (CS tests) with a repeated measure of Period (baseline vs. CS period of the test session) and a between factor of Drug (vehicle or ANI/APV).…”
Section: Methodsmentioning
confidence: 88%
“…The protein synthesis inhibitor ANI (Tocris; 10 mg) was fully dissolved in 36µl of HCl and diluted to its final concentration of 125µg/µl with 44µl of ACSF. The NMDA receptor antagonist D-APV (Tocris, 10mg) was diluted with 1000µl of ACSF to a final concentration of 10µg/µl (Kwapis et al, 2015; Kwapis et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations